Human rights and Islam : an introduction to key debates between Islamic law and international human rights law - Saeed, Abdullah, 1960- (Elgar studies in human rights, 2018)
Is there a basis for human rights in Islam? Beginning with an exploration of what rights are and how the human rights discourse developed, Abdullah Saeed explores the resources that exist within Islamic tradition in support of human rights. He identifies those that are compatible with international human rights law and can be garnered to promote and protect human rights in Muslim-majority states. Relying on significant texts in the Qur'an and hadith, early juristic discourses and modern Islamic scholarship, Saeed explains the compatibilities and incompatibilities between Islamic law and international human rights law. He also deals separately with a number of specific rights that are usually considered somewhat incompatible with Islamic law, such as the rights of women and children, freedom of expression and religion and jihad and the laws of war. Each chapter also contains a case to allow readers to look more closely at issues of relevance.-